Prevalence of extra pulmonary tuberculosis among patients registered under a district TB centre in North East India - ., Krossnunpuii; Kharkongor, Febiola (International Journal of Advances in Medicine, 2020)
Background: Worldwide, tuberculosis (TB) is one of the top 10 causes of death and the leading cause from a single infectious agent (above human immunodeficiency virus (HIV)/ acquired immunodeficiency syndrome (AIDS)). Extra pulmonary tuberculosis (EPTB) is TB outside of the lungs. In general, EPTB is more difficult to diagnose than pulmonary TB (PTB), invasive methods are often needed to obtain samples for microbiological and histological testing and in some locations treatment should be extended to avoid the appearance of relapses. The purpose of this study was to find out the prevalence of EPTB among all registered TB patients in a capital city in northeast India. Methods: A retrospective study conducted at district TB Centre (Aizawl) from data collected from patient’s treatment cards. The study period was 1 year from January 2019 to December 2019. All the registered TB patients except those registered under the programmatic management of drug-resistant TB (PMDT) were included in the study and patients registered under PMDT were excluded. All the analysis was performed using simple percentage method. Results: Out of 1502 patients, 48.8% were PTB and 51.2% were EPTB. Male comprised of 54.3% and 45.7% were Female. Majority of them (87.5%) were new patients and 10.91% were recurrent cases. History of contacts was given by 8.25% of the patients. Of the 769 EPTB cases, pleural effusion was the most common finding (350) followed by lymph nodes TB (196). Among PTB, majority of them (72.71%) were microbiologically confirmed whereas majority of the patients (84.66%) were clinically diagnosed in EPTB patients. Conclusions: This study found a high prevalence of HIV-TB co-infections, recurrent TB infection and extra pulmonary tuberculosis.